The VO2max differences based on the position roles amongst Malaysia leagues soccer athletes - Adnan, R.; Sharifudin, S. A.; Tumijan, W.; Sulaiman, N. (IEEE Colloquium on Humanities, Science and Engineering (CHUSER), 2011, 2011)
To determine the best possess of positional roles amongst Malaysia League Soccer Athletes according to Bleep and YO-YO Intermittent Endurance Test. To determine differences of VO2max level amongst Malaysia League Soccer Athletes based on three (3) positional roles (Striker (ST), Midfielder (MF) & Defender (DF)) according to Bleep and YO-YO Intermittent Endurance Test. Sixty (60) subjects from 3 professional and 1 semi- professional football clubs within Klang Valley undergoing two different types of VO2max intermittent endurance tests. Sixty (60) male subjects who participated were from PDRM FC, UiTM FC, PKNS FC, and Sime Darby FC. (21.0 ± 1.97 years old in age, 67.17 ± 6.45 kg in bodyweight and 167.23 ± 4.64 cm in height). Each soccer team provides only fifteen (15) subjects which are segregated into five (5) athletes for each three position. YO-YO Intermittent test and Bleep Test are used to measure the VO2max level for each athlete and position. Both tests measure the VO2max outcome with routine protocols. Analysis test had been used is one-way ANOVA. The findings have shown that the mean ± SD for bleep test based on their positional roles are defender (9.9 ± 1.24), midfielder (11.36 ± 1.21) and strikers (9.45 ± 1.50). The yo-yo intermittent endurance test also showed the mean ± SD for defender (1828 ± 276.25), midfielder (2212 ± 309.32) and striker (1774 ± 287.06). The VO2max level has an overall significant difference between positional roles according to bleep and yo-yo intermittent endurance tests (F (2, 57) =11.237, p < 0.001 and F (2, 57) =13.452, p <0.001). Both test shown a statistically significance difference between defender and midfielder (bleep, p = 0.004 and yo-yo, p <0 .001) and midfielder and striker (bleep, p < 0.001 and yo-yo, p <0.001). Midfielder (MF) p- sition possesses highest VO2max level compare to other two positions for both tests. There are a statistically significance difference between defender and midfielder and midfielder and strikers based on both test.